Investing ourselves: the role of space and place in being a working-class female academic. Issue 1 (2nd January 2021) - Jones, Lisa; Maguire, Meg
ABSTRACT: As working-class female academics, this paper examines the constructions of our identities focusing on both what unites and differentiates us as working-class women. We focus on the structuring forces in our lives such as our class, our whiteness and our gender, but we also discuss how our experiences have been shaped by space and place as a complex set of time-sensitive inter-relationships involving domination and subordination. Here, our different stories of where, when and how we grew up are discussed as we attempt to make sense of these in relation to our construction of class and its intersectionality with these important aspects of our lives. We examine how these shaping features of our identities influence the personal investment we place in our work and how the middle-class 'status' inferred upon us by our educational 'success' and engagement within academia almost always feels contradictory to our own subjectivities and working-class loyalties.